2013
DOI: 10.1016/j.celrep.2013.07.041
|View full text |Cite
|
Sign up to set email alerts
|

RAG2’s Acidic Hinge Restricts Repair-Pathway Choice and Promotes Genomic Stability

Abstract: SUMMARY V(D)J recombination-associated DNA double-strand breaks (DSBs) are normally repaired by the high fidelity, classical non-homologous end joining (cNHEJ) machinery. Previous studies implicated the RAG/DNA post-cleavage complex (PCC) in regulating pathway choice by preventing access to inappropriate repair mechanisms such as homologous recombination (HR) and alternative NHEJ (aNHEJ). Here we report that RAG2’s “acidic hinge”, previously of unknown function, is critical for several key steps. Mutations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 58 publications
5
56
0
Order By: Relevance
“…The mechanism by which RAG-induced DSBs are restricted to the c-NHEJ pathway is poorly understood. Since certain RAG2 mutants defined by Roth and colleagues are deficient in this process, it has been suggested that the RAG endonuclease interacts with other factor(s) that facilitate restriction of RAG-induced DSBs to the c-NHEJ pathway (34, 65, 66). We considered that the difference between DNA-PKcs-deficient cells that are proficient versus deficient in signal end joining is not because the deficient cells lack a joining factor, but because the proficient cells lack a factor that restricts RAG-induced breaks to c-NHEJ.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which RAG-induced DSBs are restricted to the c-NHEJ pathway is poorly understood. Since certain RAG2 mutants defined by Roth and colleagues are deficient in this process, it has been suggested that the RAG endonuclease interacts with other factor(s) that facilitate restriction of RAG-induced DSBs to the c-NHEJ pathway (34, 65, 66). We considered that the difference between DNA-PKcs-deficient cells that are proficient versus deficient in signal end joining is not because the deficient cells lack a joining factor, but because the proficient cells lack a factor that restricts RAG-induced breaks to c-NHEJ.…”
Section: Resultsmentioning
confidence: 99%
“…Neutralization of charge in this interval is associated with aberrant repair of RAG-mediated DNA breaks, decreased stability of RAG-signal end complexes (SECs) and genomic instability (Coussens et al, 2013). While these effects appear to reflect events occurring after RSS recognition and DNA cleavage, they may be explained in part by our results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RAG mutants have been described that enabled A-EJ to access and rejoin RAG-dependent DSBs, even in C-NHEJ proficient cells albeit to a lesser extent [140][141][142], resulting in increased translocation frequency and high incidence of lymphomas in a p53-null murine genetic background [143]. A-EJ restriction is dependent on a particular RAG2 subdomain [144]. Consequently, under normal conditions, the role of A-EJ in the V(D)J recombination is reduced to the smallest share since it is highly unlikely that the A-EJ machinery has a chance to encounter and deal with RAG-induced DSBs.…”
Section: Regulation Of A-ejmentioning
confidence: 98%